THE USE OF DRONE TECHNOLOGY IN THE AUDIT PROFESSION - Jakovljevic, Nemanja (Poslovna ekonomija, 2022)
ABSTRACT: The use of drone technology has significant potential for wider and mass application in the auditing profession, primarily in the implementation of audit engagement in the domain of the auditor’s obligation to attend the inventory if they are material from the point of view of audited financial statements. The audit of inventories aims to examine and confirm the accuracy of the statements of the responsible persons in the entity that is the subject of the audit of the financial statements of the stated inventories. The subject of research in this paper are the attitudes of persons engaged in audit work on the use of drone technology in the audit profession with an emphasis on the use of drones in order to conduct stock audits. The research was conducted through a questionnaire that was advertised through publicly available mechanisms that include social networks and business contacts. The main conclusion of the paper is that there is an interest of persons engaged in auditing for the use of drone technology in the audit profession, with concerns about the costs of its use and its legal regulation for use in auditing as evidence of management’s assertions on inventories in financial statements. There is a greater interest in the use of drone technology among audit engagements employed by large international audit firms than by audit engagements working in smaller local audit firms and auditors engaged independently.